Modern glacier and climate fluctuations reflected as geodetic mass balance, calculated using historical and UAV imagery at Fannaråkbreen in Jotunheimen, central southern Norway - Jackute, Lina (The University of Bergen, 2024)
Fannaråkbreen, a mountain glacier in southern Norway, presents immediate responses to climatic fluctuations through its mass balance, making such data important for analysing climate change and glacier state. This study estimates the geodetic mass balance of Fannaråkbreen over various periods since 1966 by subtracting surfaces modelled with conventional and Structure-from-Motion photogrammetry from historical aerial and UAV imagery. Uncertainty was addressed using geostatistics. Results indicate an accelerating mass loss, with the annual mass balance from 1966 to 2023 at -0.37 ± 0.02 m w. e., and a 36.6% total area reduction since 1955. Comparisons with Storbreen’s glaciological mass balance reveal similar patterns, with discrepancies linked to differences in glacier size, local climates and measurement techniques. Additionally, the results illustrate that Fannaråkbreen exhibits mass loss patterns and rates consistent with other continental glaciers in the region. The study also quantifies winter and summer balances at 1.10 ± 0.05 and -1.71 ± 0.09 m w. e. respectively, based on high-resolution UAV data from 2022 and 2023. These findings underscore how remotely sensed data, combined with precise co-registration methods, can assess and reconstruct glacier changes in detail remotely, offering a method to supplement global mass balance records. Masteroppgave i geografi GEO350 MASV-GEOG MASV-MEHA MASV-PHYG MPGEOGR